Polymer Reinforcement - Lipatov, Y.S. (ChemTec Publishing, 2011)
Starting with the basics of polymer adsorption, the work covers the polymer/solid interface, thermodynamics, kinetics, and viscoelastic effects, and deals in depth with polymer alloys.